Exploring art a global, thematic approach - Lazzari, Margaret R.; Schlesier, Dona (Cengage Learning, 2016)
Making art relevant to students' everyday lives, Exploring Art: A Global, Thematic Approach, 5E provides a solid foundation of art basics and then presents art from Western and non-Western cultures through themes such as religion, power and politics, sexuality, mind and body, mortality and immortality, nature and technology, and entertainment and visual culture. This thematic approach to art appreciation keeps students fully engaged in the study of art. "Art Experiences" features in every chapter and an all-new Chapter 15, "Art in Your Life," draw explicit connections between art and students' lives, illustrating how art is all around us as well as providing suggestions for interacting with art. Timelines with thumbnail images help students easily draw chronological connections between works, and detailed world maps illustrate geographical relevance. In addition to new works, the fifth edition offers expanded representation of contemporary artists from around the globe. Also available with the fifth edition, MindTap equips students with the ultimate personal learning experience through an interactive eBook, digital activities, author videos for each chapter, apps, and more. Exploring Art gives students an appreciation for artworks and art styles across time and across the globe--Publisher.